2023
DOI: 10.1186/s13229-023-00563-4
|View full text |Cite
|
Sign up to set email alerts
|

Examining the latent structure and correlates of sensory reactivity in autism: a multi-site integrative data analysis by the autism sensory research consortium

Zachary J. Williams,
Roseann Schaaf,
Karla K. Ausderau
et al.

Abstract: Background Differences in responding to sensory stimuli, including sensory hyperreactivity (HYPER), hyporeactivity (HYPO), and sensory seeking (SEEK) have been observed in autistic individuals across sensory modalities, but few studies have examined the structure of these “supra-modal” traits in the autistic population. Methods Leveraging a combined sample of 3868 autistic youth drawn from 12 distinct data sources (ages 3–18 years and representing … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 185 publications
(228 reference statements)
0
1
0
Order By: Relevance
“…Although large databases (e.g., Feliciano et al, 2018;Hall et al, 2012) are promising and likely an important step for future research, straightforward use of these samples for PROM evaluation is often precluded by a lack of clarity in sample characterization, questionable representativeness of large samples (Rødgaard et al, 2022), time-intensive data cleaning, and fraudulent responses within online surveys (Harrop et al, 2021). The pooling together of many smaller samples that utilize the same or similar measures in an integrative data analysis is one promising alternative that has previously been leveraged within the autism literature (e.g., Magiati et al, 2017;Sturm et al, 2017;Williams, Schaaf, et al, 2023).…”
Section: Difficulties Collecting Large Representative Samplesmentioning
confidence: 99%
“…Although large databases (e.g., Feliciano et al, 2018;Hall et al, 2012) are promising and likely an important step for future research, straightforward use of these samples for PROM evaluation is often precluded by a lack of clarity in sample characterization, questionable representativeness of large samples (Rødgaard et al, 2022), time-intensive data cleaning, and fraudulent responses within online surveys (Harrop et al, 2021). The pooling together of many smaller samples that utilize the same or similar measures in an integrative data analysis is one promising alternative that has previously been leveraged within the autism literature (e.g., Magiati et al, 2017;Sturm et al, 2017;Williams, Schaaf, et al, 2023).…”
Section: Difficulties Collecting Large Representative Samplesmentioning
confidence: 99%
“…11 To characterize patterns of sensory differences, various questionnaires have been developed. 12, 13 For children, specifically those with autism, sensory questionnaires mainly utilize parent-report measures. The Short Sensory Profile (SSP) 14 an abbreviated version of Dunn's Sensory Profile 15,16 evaluates sensory behaviors of children with a discriminant validity of >95% in identifying sensory processing differences.…”
Section: Introductionmentioning
confidence: 99%
“…18 The SEQ assesses hyper-and hyposensitivity but does not provide sensory modality-specific sub-scores for all five senses which are important in characterizing patterns of sensory changes. 13 Importantly, hyper-and hyposensitivity are not binary classifications or even mutually exclusive labels. For example, multiple studies have shown that individuals diagnosed with autism display both hypersensitivity and hyposensitivity, sometimes even within the same modality.…”
Section: Introductionmentioning
confidence: 99%